How active social network site use affects green consumption: A moderated mediation model - Gong, Yanping; Chen, Chunyan; Tan, Yuxuan; Tang, Danni (Frontiers in Psychology, 2023)
A growing body of literature suggests a link between the usage of social networking sites (SNSs) and green consumption. However, researchers have shown that not all types of SNS usage have the same effect on individuals; therefore, further research is necessary to comprehend the linkage between a specific SNS use type and green consumption and the mechanisms underlying these links. This study examined a moderated mediation model based on self-awareness theory to explain the “how” and “why” of the relationship between active SNS use and green consumption. An offline survey (N = 210) and an online survey (N = 348) were conducted. The results suggest that active SNS use is positively associated with green consumption via public self-awareness and that impression management motives moderate the mediating role of public self-awareness in the relationship between active SNS use and green consumption. By examining the connection between a specific type of SNS use (active SNS use) and green consumption, our study adds to the body of literature on the causes of green consumption. The results have substantial implications for future research promoting socially responsible consumption behavior.